Criminalistic characteristics and the material structure of legalization (laundry) of means obtained by criminal ways - Khlus, Alexander M. (Journal of the Belarusian State University. Law, 2019)
In the article, based on the analysis of the criminalistic characteristics of legalization (laundering) of funds obtained by criminal means, various approaches to understanding its structural elements are shown. Some shortcomings of the developed forensic characteristics of this criminal act have been revealed, for example, the absence among its independent elements of the method of committing a crime. Taking into account diverse views on the category «criminalistic characterization of crimes», the author suggests in developing a theoretical part of the private investigation methodology, to implement a different path to knowledge of the act related to the legalization of funds obtained by criminal means. It involves the identification and research in the system of this crime of material structural elements, among which it is possible to identify the following elements: the subject of the crime; object of criminal assault; means of committing a crime; the subject of the crime; the subject of criminal assault. The study of these elements in the author’s opinion is expedient to carry out taking into account the provisions of the developed and uniformly understood criminalistic characteristics of this crime.